Laser Nanostructuring for Diffraction Grating Based Surface Plasmon-Resonance Sensors - Iaroslav Gnilitskyi; Sergii V. Mamykin; Christina Lanara; Ihor Hevko; Mykhaylo Dusheyko; Stefano Bellucci; Emmanuel Stratakis (Nanomaterials, 2021)
The surface plasmon resonance properties of highly regular laser-induced periodic surface structures (HR-LIPSSs) on Si, functionalized with Au nanoparticles (NPs), were investigated. In particular, the spectral dependencies of polarized light reflectance at various angles of incidence were measured and discussed. It is found that the deposition of Au NPs on such periodically textured substrates leads to significant enhancement of the plasmon resonance properties, compared to that measured on planar ones. This effect can be used to improve the efficiency of localized-plasmon-resonance-based sensors.